Use of an Interactive, Faith-Based Kiosk by Congregants of Four Predominantly, African–American Churches in a Metropolitan Area - Dulchavsky, Scott A.; Ruffin, Wilma J.; Johnson, Dayna A.; Cogan, Chad; Joseph, Christine L. M. (Frontiers in Public Health, 2014)
Chronic diseases are prevalent in ethnic communities. Churches represent a potent resource for targeted health promotion. A Faith-Based Kiosk (FBK) was developed as an informational tool and placed in four predominantly (>80%) African-American churches. Congregants were surveyed to describe Kiosk use, kiosk-user characteristics, health status, and self-reported behavior changes attributed to the kiosk. We analyzed 1,573 questionnaires. Mean age of respondents was 46.4 years and >70% were women. “Older” congregations (mean age > 46.1 years) had more reports of diabetes (p=0.002) and heart disease (p=0.01) than younger churches (mean age < 44.1), whereas asthma was more prevalent in the latter (p< 0.001). Prevalence of obesity (40%) was similar across churches (p=0.570). Kiosk-use was reported by 420 (26.7%) respondents. Compared to non-users, kiosk-users were >40 years (p< 0.001), and reported >2 health conditions, adjusted Odds Ratio (95% Confidence Interval)=1.43 (1.0-2.0), p=0.05. Male Kiosk-users preferred to select disease-specific content, aOR=1.87 (1.10-3.17), p=0.02, while females tended to select information about supportive community resources, aOR=0.49 (0.23-1.04), p=0.062. Knowledge of Kiosk-user characteristics and the “health status” of a congregation, provide an opportunity for targeted, church-based health promotion.